The Prevalence of risk factors for Oropharyngeal Cancers in the migrants of Ahmedabad city- a comparison with the native population. - Rupesh Kumar; Bharti Koria; A. Bhagyalaxmi; Prabhakaran K (Asian Journal of Medical Research, 2013)
To assess the prevalence of risk factors for Oropharyngeal cancer among migrants of Ahmedabad city and comparing to its native population. To recommend the preventive strategies based on the study findingsA cross-sectional study was conducted consisting of 384 migrants and 384 native populations of Ahmedabad City involving it's all six zones between periods May 2009 to April 2010.384 migrants and equal number of native population of Ahmedabad city were analyzed. 36.46% of migrants & 34.11% of native population were in age group of 28- 37 years. Out of 384 migrants, 132(34.38%) were having habit of smoking where as 94(24.48%) of native population were smokers (statistically significant P<0.05). The prevalence of smokeless tobacco among migrants and native population were 89 (23.17%) and 107 (27.86%) respectively (statistically not significant p>0.05). The prevalence of alcohol intake was more among migrants (4.16%) as compared to native population (2.08%) (Statistically not significant p <0.05).Smoking, a major risk factor for Oropharyngeal cancer is significantly more in migrant population as compared to native population.